Antiepileptic drugs in migraine prophylaxis - Mazzotta, Giovanni (Springer-Verlag, 2004)
Research in the field of headache treatment has experienced a marked impetus in the last few years. In the era of the triptans, the treatment modality of this disease has been revolutionised, and though most of the studies conducted have investigated the symptomatic treatment of migraine, less attention has been dedicated to migraine prophylaxis. This review considers the current data available in the literature regarding the use of antiepileptic drugs in migraine prophylaxis, noting the clinical studies that have yielded statistically significant data.